Herbal Jelly Candy Mengkudu and Red Ginger Extract, Physicochemical and Organoleptic Properties Reviews - Vera Amanda Putri; Richardus Widodo; Tiurma Wiliana Susanti Panjaitan; Dwi Agustiyah Rosida (Agricultural Science, 2025)
Noni is a fruit that contains important nutrients such as vitamins A, C, niacin, and thiamine. Red ginger contains important compounds such as zingiberon, zingiberin, and zingibetol. Noni and red ginger can be used as jelly candy products. Jelly candy is a soft-textured confectionery that people love and is processed with the addition of hydrocolloid ingredients. This study aims to determine the effect of the combination of noni juice and red ginger on jelly candy's physicochemical and organoleptic properties. The design used was a one-factor Complete Random Design (RAL) with a comparison of noni juice and red ginger, namely P1 95:5, P2 90:10, P3 85:15, P4 80:20, P5 75:25. The results showed that the combination of noni juice and red ginger juice in jelly candy products did not have a real effect on the level of chewiness of the product. The combination of noni juice and red ginger juice in jelly candy has a very real effect on the product's moisture content and ash content, where the moisture content will increase as the concentration of noni juice increases and the concentration of red ginger juice decreases. In contrast, the ash content will increase as the red ginger juice concentration increases and the noni juice concentration decreases. The combination of noni juice and red ginger juice in jelly candy did not have a real effect on the level of color and aroma preference, but had a real effect on the level of taste and chewiness, where P4 was the most preferred by the panelists.